The Place of Mathematics in Secondary Education. National Council of Teachers of Mathematics - National Council of Teachers of Mathematics, Inc., Reston, VA.; Reeve, W. D.; National Council of Teachers of Mathematics, Inc., Reston, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1940)
This yearbook is the final report of the Joint Commission of the Mathematical Assocation of America and the National Council of Teachers of Mathematics. The report contains discussions of the following: role of mathematics in civilization, general aims of modern education, general objectives for secondary education, place of mathematics in education, curriculum, one organization of instruction, a second curriculum plan, problems of retardation and acceleration, the junior college, evaluation of pupil progress, and teacher education. The major portion of the report is devoted to discussions of general principles. In several instances, such as programs of instruction, specific proposals are presented more in the form of acceptable possibilities rather than as the only answer. (LS)
Availability: National Council of Teachers of Mathematics, Inc., 1906 Assocation Drive, Reston, Virginia 22091.
Educational level discussed: Two Year Colleges.
Keywords: Acceleration; Cultural Background; Curriculum; Educational Objectives; Educational Principles; Evaluation; Instruction; Mathematics Education; Reference Materials; Reports; Secondary School Mathematics; Teacher Education; Two Year Colleges; Yearbooks; Reports, Descriptive